Art 1975 Analysis of the Effectiveness of Restructuring in Resolving Problematic Financing in Murabahah Contracts at PT Bank Sumut KCP Syariah Simpang Kayu Besar - Putri Ahmarani; Muhammad Lathief Ilhamy Nasution; Waizul Qarni (IAI Ummul Ayman, Meureudu, Pidie Jaya, Aceh, Indonesia, 2026)
This study aims to analyze the effectiveness of restructuring in resolving problematic financing in murabahah contracts at PT Bank Sumut KCP Syariah Simpang Kayu Besar, including the implementation of restructuring, its effectiveness, compliance with sharia principles, and the obstacles encountered. This study uses a qualitative descriptive approach with field research. Data were obtained through observation, interviews, and documentation, then analyzed using data reduction, data presentation, and conclusion drawing techniques. The results show that financing restructuring through rescheduling and adjustment of payment schemes has proven effective in helping customers fulfill their obligations, improving financing quality, and keeping the increase in problematic financing under control. The effectiveness of restructuring is not only reflected in the control of the Non-Performing Financing (NPF) ratio, but also from changes in customer payment behavior and improved financing collectibility. The implementation of restructuring is also in accordance with sharia principles, especially the principles of al-taradhi, ta'awun, and justice, because it is carried out based on mutual agreement without changing the substance of the murabahah contract. Obstacles to its implementation include low customer understanding, potential moral hazard, additional restructuring costs, limited bank supervision, and external economic conditions. Therefore, restructuring can be considered an effective policy for resolving problematic financing under murabahah contracts.